2017
DOI: 10.3390/nu9030210
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Anti-Inflammatory Properties of Ganoderma lucidum Extract Effects on Melanoma and Triple-Negative Breast Cancer Treatment

Abstract: Among the most important traditional medicinal fungi, Ganoderma lucidum has been used as a therapeutic agent for the treatment of numerous diseases, including cancer, in Oriental countries. The aim of this study is to investigate the anti-inflammatory, anticancer and anti-metastatic activities of Ganoderma lucidum extracts in melanoma and triple-negative breast cancer cells. Ganoderma lucidum extracts were prepared by using common organic solvents; MDA-MB 231 and B16-F10 cell lines were adopted as cellular mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 24 publications
2
52
0
1
Order By: Relevance
“…However, among these, triterpenoids and polysaccharides (β-glucan, in particular) are the most important components that contribute to anticancer functions. 15,[47][48][49] G. lucidum extracts present an anticarcinogenic effect on different cancer cell lines. 10 Recent studies demonstrate many mechanisms where G. lucidum extracts present anticancer activities.…”
Section: Health Effectmentioning
confidence: 99%
See 3 more Smart Citations
“…However, among these, triterpenoids and polysaccharides (β-glucan, in particular) are the most important components that contribute to anticancer functions. 15,[47][48][49] G. lucidum extracts present an anticarcinogenic effect on different cancer cell lines. 10 Recent studies demonstrate many mechanisms where G. lucidum extracts present anticancer activities.…”
Section: Health Effectmentioning
confidence: 99%
“…10 Recent studies demonstrate many mechanisms where G. lucidum extracts present anticancer activities. 10,49 Such mechanisms are summarized as follows:…”
Section: Health Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…These immunomodulatory properties primarily depend on the source they have been extracted from; studies conducted in animals and humans and confirmed that the oral administration of yeast β-glucans had a greater effect on the immune system than grain-derived β-glucans (Vetvicka and Vetvickova, 2016). β-glucan is active in all species from earth-worms to humans, and is able to stimulate humoral and cellular immunity (Novak and Vetvicka, 2008) and inhibit the development of cancer (Sima et al, 2015, Barbieri et al, 2017. Prebiotic β-glucan has no harmful effect on liver and kidney functions and can be considered as immunopotentiator (immunostimulant) due to its stimulation of immune system and it has ability to reduce the adverse effect of microbial infection in rats (Somia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%